A study on microbial profile and antibiotic resistance in pediatric intensive care unit in a tertiary care hospital - K M Anil Kumar,; Hiremath Sagar, (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to compare the microbial profile and antibiotic resistance pattern of isolates from pediatric intensive care unit (PICU) after dividing them as isolates detected within 48 h of admission and isolates detected after 48 h in PICU. Materials and Methods: This retrospective observational study was performed in a single tertiary care hospital’s PICU for a period of 3 years from July 2016 to June 2019. The total number of cultures sent, type of specimen, number of positive cultures in different specimens, culture isolates and their antibiotic resistance, and sensitivity pattern were noted. Positive cultures were divided as admission isolates if detected from cultures sent within 48 h of admission and as PICU acquired isolate if detected from cultures sent after 48 h of admission to PICU. The epidemiological characteristics of these isolates and their antibiotic susceptibility were compared. Results: A total of 3157 cultures were sent and positive cultures were 345 (10.8%). Admission isolates were 147 (4.6%) and PICU-acquired isolates were 198 (6.2%). Tracheal secretions had the highest yield with 35.6% of the cultured specimen being positive. The most common admission isolates were Escherichia coli (18.3%), Staphylococcus aureus (15.3%), and Klebsiella pneumoniae (12.2%). The most common PICU acquired isolates were K. pneumoniae (19.1%), E. coli (16.6%), Pseudomonas aeruginosa (15.6%), and Acinetobacter baumannii (9.6%). The number of drug-resistant strains multidrug-resistant (MDR) (MDR Acinetobacter, MDR E. coli, and MDR Klebsiella) was significantly higher in PICU-acquired isolates (p